Strategi Rusia dalam Kontra-Terorisme di Kaukasus Utara pada Periode Pemerintahan Vladimir Putin - Carmelita Angeline (Jurnal Ilmu Hubungan Internasional LINO, 2022)
The North Caucasus is a mountainous region on the border of Russia and Asia. The Caucasus region has been a conflict area since the days of the Russian Empire. The intensity of conflict in the region requires Russia to intervene to stabilize security in the North Caucasus. Rebel groups in the North Caucasus are demanding independence in order to break away from the Russian Federation, but Russia is not that easy to let go. This rebel group developed into a terrorist group and began to launch theoretical attacks on Russia. This is Russia's most important internal security problem. President Vladimir Putin began to carry out counter-terrorism operations in the North Caucasus in various ways, such as making policies and cooperating with other countries. Defense policy is a desire to uphold security values ​​in a nation. This theory is important in Russia's counter-terrorism efforts followed by an understanding of terrorism and counter-theorism to maximize defense policy-making. In making this research, the researchers collected sources from books, journals and the internet to support the results of interviews with experts. This study focuses more on analyzing descriptively how Russia's success in counter-terrorism in the North Caucasus. From Russia's policy of counter-terrorism operations to the exclusion of human rights, this has been less effective and has received international criticism. Then, Russia began to prioritize infrastructure development in the North Caucasus with the aim of boosting the economy, giving autonomy to the Caucasus under Russian control to grant political rights and stabilize politics in the region. Although Russia's cooperation with other countries has experienced ups and downs, all of Russia's counter-terrorism efforts in the North Caucasus can be said to be quite effective and in accordance with Russia's defense policy.